Taekwondo Athlete’s Level of Special Physical Condition - wahyuni, silvia; umar, umar; Irawadi, Hendri; Setiawan, Yogi (Universitas Negeri Padang, 2022)
In this study, the problem that can be seen is the decline in achievement obtained by Taekwondo athletes Dojang UNP. This study aims to determine the extent of the physical condition of the taekwondo athletes at Dojang UNP. Researchers conducted research on Taekwondo athletes Dojang UNP. This type of research is descriptive. This research was conducted in the parking lot of the Al-Azhar Mosque UNP Padang in January and February 2021. The population of this study was 35 people. The sampling technique used purposive sampling technique, so the number of samples in this study were 10 people, 5 male athletes and 5 female athletes. The instrumentation in this study are: 1) vertical jump test, 2) flexion of trunk, and 3) bleep test. The data analysis technique used in this study was the percentage descriptive analysis technique p = f / n × 100%. The results of this study were: 1) The level of leg muscle explosions of the Taekwondo athlete Dojang UNP Padang was in the moderate category. 2) The level of flexibility of the Taekwondo athletes of UNP Padang is in the Medium category. 3) The aerobic endurance level of the taekwondo athletes of UNP Padang is in the medium category.